Pengaruh Perputaran Piutang dan Perputaran Persediaan terhadap Profitabilitas (Studi Empiris pada Perusahaan Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2015-2018) - Yanti Yanti; Mumun Maemunah (Universitas Muhammadiyah Metro, 2020)
The aim of this study is to determine the accounts receivable turnover rate and inventory turnover have an influence on profitability both partially and simultaneously in a company. The object of this study is a consumer goods industry sector manufacturing company that listed on Indonesia Stock Exchange in the period 2015-2017. The type of data in this study is quantitative data. The source of the data in this study is secondary data, in the form of financial report data (balance sheet and income statement) related to variable in this study. The results of this study indicates that accounts receivable turnover has an affect on profitability. While inventory turnover does not affect on profitability. The results of the study simultaneously indicates that accounts receivable turnover and inventory turnover influence together on profitability.